Blue collar, theoretically a post-marxist approach to working class literature - Lavelle, John F., 1950- (McFarland & Co., 2012)
"This critical work seeks to establish a new philosophy of class, drawing on disciplines as diverse as sociology, cognitive science, anthropology and psychology and applying a decidedly Weberian hermeneutical lens. Topics covered include a detailed exploration of Marxism, a review of working class literature, post-marxist theories of class and the future of the field"--Provided by publisher.